2015
DOI: 10.1109/tdei.2015.7116324
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surface fluorination on dielectric properties and surface charge behavior of water absorbed polyimide film

Abstract: With the advantages of excellent physical, chemical and thermal properties, polyimide (PI) film has been widely used as insulation material in electrical and mechanical equipment. However, PI presents water absorption capacity because of the existence of carbonyl and amine groups in the molecular chain. When exposed in moisture conditions, PI film will be degraded. Therefore, the dielectric breakdown occurs and irremediable damage will appear in insulation system. The dielectric properties of PI film are large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Optimization of the wetting ability of polymer surfaces by fluorination is promising for use in offset printing [30,40,41], ensuring the protective properties of polymer materials [29,[42][43][44][45][46], membrane [27,47]; and sorbents [38] performance. Direct fluorination of polymers also results in the formation of deep and shallow charge traps on a surface that improves dielectric [48][49][50][51], piezoelectric [52,53] properties, surface conductivity [54,55], breakdown [48,56], and DC flashover [57][58][59][60][61][62] voltages.…”
Section: Introductionmentioning
confidence: 99%
“…Optimization of the wetting ability of polymer surfaces by fluorination is promising for use in offset printing [30,40,41], ensuring the protective properties of polymer materials [29,[42][43][44][45][46], membrane [27,47]; and sorbents [38] performance. Direct fluorination of polymers also results in the formation of deep and shallow charge traps on a surface that improves dielectric [48][49][50][51], piezoelectric [52,53] properties, surface conductivity [54,55], breakdown [48,56], and DC flashover [57][58][59][60][61][62] voltages.…”
Section: Introductionmentioning
confidence: 99%
“…By analyzing these, we can observe an increase in conduction current in the case of fillers added in the polyimide matrix at low temperature, but we observe a conduction current decrease for nanocomposite samples at high temperature. All the films expose the same trend of conduction current profile at low electric fields (<16 kV/mm), in which the conductivity of single-layer PI/SiO 2 and fluorinated samples (FPI) is higher than the pure PI and multilayer PI-PI/SiO 2 films at low electric fields [ 47 , 48 , 49 ]. Higher conductivity can help to release trap charges [ 48 , 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…All the films expose the same trend of conduction current profile at low electric fields (<16 kV/mm), in which the conductivity of single-layer PI/SiO 2 and fluorinated samples (FPI) is higher than the pure PI and multilayer PI-PI/SiO 2 films at low electric fields [ 47 , 48 , 49 ]. Higher conductivity can help to release trap charges [ 48 , 50 , 51 ]. As shown in Figure 6 , we observed that the films have at least two to three types of conduction from the slope of the current density J, relying on the applied electric field and temperatures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9] Preceding theoretical researches showed that surface morphology and chemical element of insulating materials can affect the motion characteristics of surface charges, and then influence the flashover. [10][11][12][13] At present, methods for surface modification of polymers including surface group modification, surface fluorination, oxide film surface deposition, changing the surface morphology of materials, and organic coating synthesis. The surface group modification means variation of physical and chemical properties for polymer surface through introducing functional groups.…”
Section: Introductionmentioning
confidence: 99%